2014
DOI: 10.1016/j.jalz.2014.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dementia in urban and regional Aboriginal Australians

Abstract: Consistent with previous findings in a remote population, urban and regional Aboriginal Australians face high rates of dementia at younger ages, most commonly Alzheimer's dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
128
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(140 citation statements)
references
References 25 publications
6
128
1
5
Order By: Relevance
“…Studies are repeatedly reporting much higher rates of dementia in Aboriginal Australians, compared with nonIndigenous Australians, with rates amongst the highest in the world [16][17][18]. A longitudinal study of indigenous people living in rural and remote areas of the Kimberley, Western Australia had a dementia prevalence of 14.8% [16] and a study of indigenous people living in urban and regional New South Wales found a prevalence of 13.4%, agestandardised to 21%, compared with the overall Australian prevalence of 6.8% [17]. The Aboriginal population has an overwhelming burden of poor health outcomes, cardiovascular risk factors, drug and alcohol abuse, educational, employment and social hardships [19].…”
Section: Epidemiological Studies In Oceaniamentioning
confidence: 99%
“…Studies are repeatedly reporting much higher rates of dementia in Aboriginal Australians, compared with nonIndigenous Australians, with rates amongst the highest in the world [16][17][18]. A longitudinal study of indigenous people living in rural and remote areas of the Kimberley, Western Australia had a dementia prevalence of 14.8% [16] and a study of indigenous people living in urban and regional New South Wales found a prevalence of 13.4%, agestandardised to 21%, compared with the overall Australian prevalence of 6.8% [17]. The Aboriginal population has an overwhelming burden of poor health outcomes, cardiovascular risk factors, drug and alcohol abuse, educational, employment and social hardships [19].…”
Section: Epidemiological Studies In Oceaniamentioning
confidence: 99%
“…Recent studies in the Kimberley [4], New South Wales [5] and the Northern Territory [6] have demonstrated that dementia occurs at up to five times the rate of the general population. The rates within the Aboriginal population are slightly higher in remote compared with regional and urban areas.…”
Section: Introductionmentioning
confidence: 99%
“…Art centres are acknowledged as central to the social, cultural and economic well-being of many artists and communities [13]. Artists aged over 55 years are estimated to comprise around 30% of the remote artist population [13], while the number with dementia is unknown; the evidence suggests the numbers are likely to be significant [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…4 Despite these limitations, a brief or rapid review involving one relevant database over a recent five year period provides useful information on the quantity of research produced in a given setting which was the aim of the review by Eades et al 4 Moreover, one evaluation of four rapid reviews found that their findings, while not as extensive, did not differ greatly from four completed systematic reviews on the same topics. 101 Cross-sectional design Yes a Gardner et al 2015 102 Cross-sectional design No Lalla et al 2015 103 Cross-sectional design Yes Radford et al 2015 104 Cross-sectional design Yes Hopkins et al 2015 105 Cross-sectional design No Arjunan et al 2015 106 Cross-sectional design No Katzenellenbogen et al 2015 107 Cross-sectional design No Pearce et al 2015 108 Cross-sectional design No Spurling et al 2014 109 Cross-sectional design Yes a Scott et al 2014 110 Cross-sectional design No Timms et al 2014 111 Cross-sectional design No Chung et al 2014 112 Cross-sectional design Yes Askew et al 2013 113 Cross-sectional design Yes a Lopez et al 2014 114 Cross 141 Qualitative Yes 153 Mixed methods Yes Gould et al 2015 154 Mixed methods No Jersky et al 2015 155 Mixed methods No Dennis et al 2015 156 Mixed methods No Govil et al 2014 157 Mixed methods Yes Thomas et al 2013 158 Mixed methods No Canuto et al 2013 159 Mixed methods No Homer et al 2012 160 Mixed methods No Larkins et al 2011 161 Mixed methods No Harris et al 2014 162 Cohort study No McDonald et al 2014 163 Cohort study No Jamieson et al 2013 164 Cohort study No Knight et al 2013 165 Cohort study No Webster et al 2013 166 Cohort study No Davis et al 2012 167 Cohort study No Robinson et al 2012 …”
Section: Sparse Research In Urban Populationsmentioning
confidence: 99%
“…Biddle recommends taking the most efficient approach possible to data collection and analysis in order to minimise participant burden. 180 In summary, research data published in the last five years and indexed on PubMed, 107 Aboriginal health liaison 8,041 b No O'Connor et al 115 Chlamydia 7,103 b Yes Dutton et al 170 Health 128 Albuminuria 860 No Lopez et al 114 Ischaemic heart disease 833 b Yes Hopkins et al 105 Psychological resilience 677 No Arjunan et al 106 Tobacco use 663 No Jamieson et al 164 Oral 113 Stressful events in children 344 b No Lalla et al 103 Oral mucosal disease 342 No Radford et al 104 Dementia 336 No Whish-Wilson et al 99 Birth outcomes 301 Yes Roberts-Thomson et al 117 Oral health 251 No Dorrington et al 174 Pap smears 213 No Gardener et al 102 Children 205 No Wong et al 126 Midwifery 177 Infant health 175 Yes Luke et al 181 Suicidal 169 Breast feeding 159 Yes Webster et al (Gudaga study) 166 Child growth 157 No Scott et al 110 Sexual health 155 No Miller et al (Gudaga study) 118 Child language assessment 150 No Arrow 100 Oral …”
Section: Sparse Research In Urban Populationsmentioning
confidence: 99%